2019
DOI: 10.1590/1806-9282.65.6.909
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between cephalic circumference at birth and ocular alterations in patients with microcephaly potentially associated with Zika Virus infection

Abstract: SUMMARY INTRODUCTION: The Zika virus (ZIKV) is an arbovirus isolated for the first time in 1947 and transmitted to humans by the Aedes aegypti mosquito. In Brasil, it was first detected in May 2015. Since then, ZIKV has been identified as the etiological agent of acute exanthematous disease in Brasil, and Neuropediatricians of the Recife warned about an epidemic of microcephaly, and the Brazilian Ministry of Health confirmed the association between ZIKV and Congenital malformations and neurological syndromes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…Only two studies (12.5%) (11,23) showed signs suggestive of sensorineural changes: in both, nearly 17% of children had hearing loss. Other evidence in this review was visual acuity abnormalities, reported in eight studies (43.7%) (11,(13)(14)(18)(19)23) . In a cohort of 173 children with microcephaly, 30% presented abnormalities in vision; of these, 50% had nystagmus (19) .…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Only two studies (12.5%) (11,23) showed signs suggestive of sensorineural changes: in both, nearly 17% of children had hearing loss. Other evidence in this review was visual acuity abnormalities, reported in eight studies (43.7%) (11,(13)(14)(18)(19)23) . In a cohort of 173 children with microcephaly, 30% presented abnormalities in vision; of these, 50% had nystagmus (19) .…”
Section: Discussionmentioning
confidence: 83%
“…The primary studies grouped in this review showed evidence of exposure to ZIKV in the fetal period and the post exposure effects in newborns (NBs) and breastfeeding children. Neurological abnormalities and/or congenital malformations were present in all studies (5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) . Microcephaly (62.8%) (5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) was predominant, however other studies have reported the occurrence of alterations in the central nervous system and multiple malformations (12,(21)(22)(23)(24)(25) .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations